Quality control and interest of the determination of anti-CCP antibodies and rheumatoid factor in the diagnosis of rheumatoid arthritis (Asian Journal of Medical and Biological Research, 2016)
The rheumatoid arthritis (RA) is an auto-immune, rheumatic and chronic inflammatory disease, characterized by joints damage. The early diagnosis of RA allows the initiation of a treatment which offers to the patients more chance of remission and avoids the evolution towards the unrecoverable deformity of joints. The objective of this study is to evaluate the performance of recent tests for the determination of anti -CCP antibodies and FR by ELISA in Benin Republic. This analytical, retrospective (2 years 6 months) and prospective (7 months) study allowed us to collect 36 patients meeting the American College of Rheumatology (ACR) criteria for RA and 24 controls. A comparison was made with the latex agglutination test for rheumatoid factors and a search of rheumatoid factors (RF) on the one hand and anti-cyclic citrullinated peptide. In our study, the specificity of anti-CCP assay (100 %) is higher than that of RF-ELISA (91.7%). The sensitivity of RF-ELISA assay is higher (77.8 %) than that of anti-CCP assay (66.7%). The latex test for rheumatoid factors has a sensitivity of 33.3 %. The positive predictive value (PPV) of anti-CCP assay (100 %) is higher than that of RF-ELISA assay (93.33 %). The positive-likelihood ratio (LR+) of anti-CCP assay is higher than the LR+ of RF-ELISA assay (4.96). The negative-likelihood ratio (LR-) of anti-CCP assay (0.33) is higher than the LR- of RF-ELISA assay (0.24). In conclusion, the anti-CCP assay has the highest specificity and RF-ELISA assay shows the highest sensitivity. In conclusion, the association of the two assays enhances a better diagnosis value for RA.Asian J. Med. Biol. Res. September 2016, 2(3): 379-388